Socio-Cultural Determinants of Drug Use - Kljajević, Srđan (Zbornik Instituta za kriminološka i sociološka istraživanja, 2017)
Drug use is a widespread phenomenon in geographical and historical terms. Socio- cultural context plays a significant role in influencing the form of drug use. The impact of contemporary culture on drug use can be seen in terms of specific cultural influences and the wider context of Western culture. Cultural influences are mediated by factors of social structure. The phenomenon of globalization has contributed to the spread of Western culture of risk factors associated with the use of drugs to other parts of the world. The aim is to show the most important sociocultural etiological factors for drug use, as well as a critical review of the previous efforts of society in terms of dealing with this phenomenon.